Establishment of pancreatic cancer zebrafish xenografts for personalized medicine in oncology practice - Barroso, Mariana Isabel Tavares (2021)
Tese de mestrado, Oncobiologia, Universidade de Lisboa, Faculdade de Medicina, 2021